Localized states and quantum effect of photo-generated carriers in photovoltaic system - Wei-Qi Huang (Nature Portfolio, 2017)
Abstract We have fabricated the multiple nanolayers impuritied on silicon pillars for Si solar cells to pick up photons in ultraviolet and infrared region of solar spectra, in which the localized states originated from nanosilicon doped with oxygen are built to avoid Auger recombination, and some interesting quantum phenomena in the localized states have been observed. The quantum effect of photo-generated carriers has been observed in I-V curve measurement on the photovoltaic sample prepared in oxygen by using nanosecond pulsed laser. More interesting, the twin states of quantum vibration are measured in the localized states originated from the impuritied nanosilicon, which provides a stable reservoir for electrons in the photovaltaic system. It should be noted that the amplitude change of the quantum vibration occurs under magnetic field with 0.33T on the sample prepared in oxygen, owing to the electron spin in the localized states. The photoluminescence (PL) spectra measured from 300 nm to 1700 nm exhibit the localized states in various regions in the photovoltaic system, in which the electrons can stand in the localized states with longer lifetime to be uneasy into Auger recombination.